Contact Modeling for Solids and Particles - Popp, Alexander; Wriggers, Peter; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
The book conveys modern techniques and the latest state-of-the-art with regard to the most fundamental aspects of computational contact mechanics. However, since contact can readily be interpreted as a special type of interface problem, it seems advisable not to isolate contact mechanics, but rather to address it in the context of a broader class of problems denoted as computational interface mechanics. The book gives a clear understanding of the underlying physics of interfaces, and a comprehensive insight into the current state-of-the-art and selected cutting-edge research directions in the computational treatment of interface effects. It focuses on the modeling of friction, wear, lubrication, cohesive interfaces, grain boundaries, phase boundaries, fracture, thermo-mechanics and particulate contact (e.g. granular media). Also the most important computational aspects are addressed, including discretization techniques for finite deformations, solution algorithms for single- and multi-processor computing environments, multi-scale approaches, discrete element models and multi-physics problems including contact and interface constraints. Among the computational techniques covered in this book are finite element (FEM) and boundary element (BEM) methods, atomistic models, molecular dynamics (MD), discrete element methods (DEM), coupling approaches for multi-scale simulations, and tools for an efficient automated FEM code generation.
Multi-scale approaches in interface mechanics -- Physics of contact across scales: nano-, meso-, macro-scale -- Computational methods for finite deformation contact mechanics -- Wear, lubrication and micromechanics of interfaces modeling and simulation of contact -- Emerging computational techniques in contact and interface mechanics -- Multiphysics, discrete elements and granular media. .
Keywords: Mechanics, Applied; Solids; Mathematical models; Surfaces (Physics).; Surfaces (Technology).; Thin films; Solid Mechanics; Mathematical Modeling and Industrial Mathematics; Surface and Interface and Thin Film; Surfaces, Interfaces and Thin Film